Age, origin and tectonothermal modification of the Falun pyritic Zn-Pb-Cu-(Au-Ag) sulphide deposit, Bergslagen, Sweden - Kampmann, Tobias Christoph (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2017)
The Falun pyritic Zn-Pb-Cu-(Au-Ag) sulphide deposit, situated in the Palaeoproterozoic (1.9–1.8 Ga) Bergslagen lithotectonic unit in the south-western part of the Fennoscandian Shield, is one of the major base and precious metal sulphide deposits in Sweden. Felsic volcanic rocks and limestone hosting the deposit, as well as their hydrothermally altered equivalents and the mineralization, were affected by heterogeneous ductile strain and metamorphism under low-pressure, lower amphibolite-facies conditions during the Svecokarelian orogeny (2.0–1.8 Ga). These processes reworked the mineral assemblages of the original hydrothermal system and the mineralization, and also reshaped the structural geometry of the deposit. A three-dimensional modelling approach has been used in order to evaluate geometric relationships between lithologies at the deposit. The polyphase character (D1 and D2) of the strong ductile deformation at Falun is apparent. The main rock-forming minerals in the altered silicate-rich rocks are quartz, biotite and anthophyllite with porphyroblasts of cordierite and garnet, as well as retrogressive chlorite. Major static grain growth occurred between D1 and D2, inferred to represent the peak of metamorphism, as well as after D2 with growth (or recrystallization) of anthophyllite. A major shear zone with chlorite, talc and disseminated sulphides bounds the pyritic Zn-Pb-Cu-rich massive sulphide mineralization to the north, the latter being surrounded elsewhere by disseminated to semi-massive Cu-Au mineralization. F2 sheath folding along axes plunging steeply to the south-south-east is suggested as a key deformation mechanism, accounting for the cone-shaped mineralized bodies, which pinch out at depth, and explaining the similar character of intensely altered rocks on all sides of the massive sulphide mineralization. Immobile-element lithogeochemistry suggests that they share a common volcanic precursor. These relationships are consistent with a model in which the pyritic massive sulphide mineralization ...